Training the Endoscopy Trainer: From General Principles to Specific Concepts - Sylvain Coderre; John Anderson; Alaa Rostom; Kevin McLaughlin (Canadian Journal of Gastroenterology)
Endoscopy instruction has progressed a great deal in recent years, evolving from the age-old dictum of ‘see one, do one’ to the current skillful application of sound educational principles. Some of these educational principles are generic and applicable to the teaching of any content at all levels, while others are quite specific to technical skills training. The present review summarizes these important principles under the following headings: creating a learner-centred curriculum; delivering an achievable learning task; and moving from theory to practice. The present article challenges national gastroenterology organizations to embrace these concepts in structured, outcome-based educational programs.